Redesain Lembaga Kepresidenan untuk Mengatasi Ketidakseimbangan Kekuasaan Eksekutif dan Legislatif di Indonesia - M. Mustofah Bisri (Fakultas Hukum Universitas Islam Indonesia, 2025)
The presidential system of government in Indonesia faces various challenges, including the fragmentation of power between the executive and legislative branches that hampers the effectiveness of public policy. The purpose of this study is to analyze the legal challenges faced by the presidential system and how institutional redesign can strengthen the checks and balances mechanism between the executive and legislative branches. The research method used is a qualitative method with a literature study approach, where data is collected from various sources such as books, scientific journals, and official documents. The results of the study indicate that the imbalance of power makes it difficult for the president to implement government programs. The proposed institutional redesign includes clarifying the president's authority, reducing dependence on DPR approval, and simplifying the structure of the presidential institution to increase efficiency. The discussion emphasizes the importance of inter-institutional coordination and structured institutional reform to achieve government stability and effectiveness. The conclusion of this study is that appropriate institutional reform can strengthen the presidential system and improve governance in Indonesia.